Characterization of subsurface media from locations up- and down-gradient of a uranium-contaminated aquifer. (September 2020) - Moon, Ji-Won; Paradis, Charles J.; Joyner, Dominique C.; von Netzer, Frederick; Majumder, Erica L.; Dixon, Emma R.; Podar, Mircea; Ge, Xiaoxuan; Walian, Peter J.; Smith, Heidi J.; Wu, Xiaoqin; Zane, Grant M.; et al.
Abstract: The processing of sediment to accurately characterize the spatially-resolved depth profiles of geophysical and geochemical properties along with signatures of microbial density and activity remains a challenge especially in complex contaminated areas. This study processed cores from two sediment boreholes from background and contaminated core sediments and surrounding groundwater. Fresh core sediments were compared by depth to capture the changes in sediment structure, sediment minerals, biomass, and pore water geochemistry in terms of major and trace elements including pollutants, cations, anions, and organic acids. Soil porewater samples were matched to groundwater level, flow rate, and preferential flows and compared to homogenized groundwater-only samples from neighboring monitoring wells. Groundwater analysis of nearby wells only revealed high sulfate and nitrate concentrations while the same analysis using sediment pore water samples with depth was able to suggest areas high in sulfate- and nitrate-reducing bacteria based on their decreased concentration and production of reduced by-products that could not be seen in the groundwater samples. Positive correlations among porewater content, total organic carbon, trace metals and clay minerals revealed a more complicated relationship among contaminant, sediment texture, groundwater table, and biomass. The fluctuating capillary interface had high concentrations of Fe and Mn-oxides combined with trace elements including U, Th, Sr, Ba, Cu, and Co. This suggests the mobility of potentially hazardous elements, sediment structure, and biogeochemical factors are all linked together to impact microbial communities, emphasizing that solid interfaces play an important role in determining the abundance of bacteria in the sediments. Highlights: Groundwater was high in sulfate and nitrate. Sediment pore water was high in sulfate- and nitrate-reducing bacteria. High Fe and Mn-oxides combined with trace elements of U, Th, Sr, Ba, Cu, and Co. Toxic elements mobility, sediment structure, and biogeochemical factors are linked. Solid interfaces determine the abundance of bacteria in sediments.